Similarities and differences of degree of adjective in English and Uzbek languages - Ro'ziqulova Dinora Shavkatovna, Muxamadiyev Aziz Shavkatovich (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The examination of the degree of adjectives is a subject of considerable academic interest, as it offers valuable insights into the similarities and differences of adjectives. This article aims to explore the perspectives of both English and Uzbek scholars on this linguistic phenomenom. By delving into relevant theories and drawing upon examples from English and Uzbek literature, we endeavor to compare and contrast the terminologies and approaches employed in each language.